Regulation of S100A8/A9 (Calprotectin) Binding to Tumor Cells by Zinc Ion and Its Implication for Apoptosis-Inducing Activity - Yuichi Nakatani; Masatoshi Yamazaki; Walter J. Chazin; Satoru Yui (Mediators of Inflammation)
S100A8/A9 (calprotectin), which is released by neutrophils under inflammatory conditions, has the capacity to induce apoptosis in various cells. We previously reported that S100A8/A9 induces apoptosis of EL-4 lymphoma cells via the uptake of extracellular zinc in a manner similar to DTPA, a membrane-impermeable zinc chelator. In this study, S100A8/A9-induced apoptosis was examined in several cell lines that are weakly sensitive to DTPA, suggesting S100A8/A9 is directly responsible for apoptosis in these cells. Since zinc inhibits apoptosis of MM46, one of these cells, the regulation by zinc of the capacity of S100A8/A9 to bind MM46 cells was studied. When MM46 cells were incubated with S100A8/A9 in standard or zinc-depleted medium, the amounts of S100A8/A9 bound to cells was markedly lower at 3 h than at 1 h. In contrast, when MM46 cells were incubated with S100A8/A9 in the presence of high levels of zinc, binding to cells was the same at 1 and 3 h. When the cells were permeabilized with saponin prior to analysis, a larger amount of cell-associated S100A8/A9 was detected at 3 h. The amount was further increased in cells treated with chloroquine, suggesting that S100A8/A9 was internalized and degraded in lysosomes. Although it has been reported that S100A8/A9 binds to heparan sulfate on cell membranes, the amount of S100A8/A9 bound to MM46 cells was not reduced by heparinase treatment, but was reduced by trypsin treatment. These results suggest that S100A8/A9 induces apoptosis by direct binding to MM46 cells, and that this activity is regulated by zinc.